Experiences and Motivations Underlying Wishes to Die in Older People Who Are Tired of Living: A Research Area in its Infancy. (October 2014) - van Wijngaarden, Els; Leget, Carlo; Goossensen, Anne
The wish to die in older people who are tired of living and the possibilities to organize death are currently being discussed within the debate on self-determination and physician-assisted suicide. Until now insight into the experiences and thoughts of people who are tired of life but not suffering from a severe depression or a life-threatening disease is lacking. Studies focussing specifically on this topic are rare. This review provides an overview of this research area in its infancy. The existential impact of age-related loss experiences play an important role in developing a wish to die. Other influencing factors are: personal characteristics, biographical factors, social context, perceptions and values. Further research to experiences and motivations underlying these specific age-related wishes to die and the existential impact of the loss-experiences seems necessary to deepen the understanding of this group of older people and for the development of policy and good care.